The safe and effective use of methylphenidate in the psychiatric treatment of an adolescent with Epidermolysis Bullosa - Ozalp Ekinci; Tanju Celik; Asena Cigdem Dogramaci; Fevziye Toros (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Epidermolysis Bullosa is a group of inherited dermatological disorder with severe clinical symptoms. Children and adolescents with epidermolysis bullosa have been reported to experience psychosocial problems in addition to the symptoms associated with epidermolysis bullosa. Although children and adolescents with epidermolysis bullosa commonly have psychiatric symptoms, limited research has been conducted on the psychiatric treatment options. In this case report, psychiatric treatment and the safe and effective use of methylphenidate in the treatment of attention deficit hyperactivity disorder in an adolescent with epidermolysis bullosa will be discussed. [Cukurova Med J 2013; 38(3.000): 487-491]